2020
DOI: 10.15419/bmrat.v7i9.631
|View full text |Cite
|
Sign up to set email alerts
|

Clinical symptoms, endoscopic imaging and stroboscopic imaging in patients with laryngeal fungal infection : An evaluation in 48 patients

Abstract: Introduction: Aspergillus fumigatus and Candida albicans are the most common pathogenic fungi found in Vietnam. Fungal laryngitis has yet to be thoroughly investigated due to the rarity of the disease. This study aimed to describe the clinical, endoscopic and stroboscopic imaging characteristics among patients with fungal laryngitis. Methods: A cross-sectional study was performed on 48 patients diagnosed with fungal laryngitis at the Endoscopy Department of the National Ear- Nose-Throat Hospital of Vietn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Literature on invasive fungal infections of the oral cavity and the ear is limited and primarily based on literature reviews. In both locations, Aspergillus and Candida are consistently cited as the most common organisms, particularly affecting immunocompromised individuals [28][29][30]. In our case series, 97% (86 out of 89) of oral cavity fungal infection were non-invasive and caused by Candida colonization.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Literature on invasive fungal infections of the oral cavity and the ear is limited and primarily based on literature reviews. In both locations, Aspergillus and Candida are consistently cited as the most common organisms, particularly affecting immunocompromised individuals [28][29][30]. In our case series, 97% (86 out of 89) of oral cavity fungal infection were non-invasive and caused by Candida colonization.…”
Section: Discussionmentioning
confidence: 57%
“…These infections were associated with specific risk factors, including penetrating injuries, hematologic malignancies, immunosuppressive medications, and HIV/AIDS. A large series of laryngeal fungal infections in Vietnam (n=48) revealed that Aspergillus was the most common causative organism, followed by Candida [28]. Notably, all patients in this series were immunocompetent, 44% were smokers, and the infections were attributed to environmental exposure.…”
Section: Discussionmentioning
confidence: 85%
“…These infections were associated with specific risk factors, including penetrating injuries, hematologic malignancies, immunosuppressive medications and HIV/AIDS. A large series of laryngeal fungal infections in Vietnam (n = 48) revealed that Aspergillus was the most common causative organism, followed by Candida [21]. Notably, all patients in this series were immunocompetent, 44% were smokers and the infections were attributed to environmental exposure.…”
Section: Discussionmentioning
confidence: 85%